Relationship between obesity and cognitive intelligence in junior high school students - Novysan Montolalu; H. A. Tangkilisan; Nelly Mayulu (Paediatrica Indonesiana, 2009)
Background Obesity is a global health problem. This conditionmay cause negative impacts on children's cognitive function. Early detection of obesity may lessen these impacts.Objective To determine the relationship between obesity statusand cognitive intelligence in children.Methods A cross sectional study was conducted for two months0 une to July 2008) on 7'h grade students at three Junior HighSchools in the Wenang subdistrict of Manado City, Indonesia.We included children aged 12-13 years, registered in 2007-2008,who gave parental consent, and who suffered from obstructivesleep apnea syndrome (OSAS) and hypertension. We excludedchildren who were sick at the time of the study, suffered fromepilepsy, attention deficit hyperactivity disorder (ADHD),congenital heart disease, or malnutrition. Data were analyzedusing Somers' D Test.Results There were 52 boys out of 100 subjects studied. Fifty eight students (58%) had a normal BMI, and 42 were obese (36 with mild obesity, and 6 with moderate obesity). Out of the 42 obese students, 1 o/o had a defective IQ, 1 o/o had a below average IQ, 22% had an average IQ, 7% had an above average IQ and 11 o/o had a superior IQ. From 58 subjects with a normal BMI, none had a below average IQ, 20% had an average IQ, 18% had an above average, and 20% had a superior IQ. The mean IQ scores for obese and non-obese subjects were 108.7 and 114.1 respectively.Conclusion Obesity has relationship with cognitive intelligencein junior high school students.